Comparison of Airway Pressure Release Ventilation to High-Frequency Oscillatory Ventilation in Neonates with Refractory Respiratory Failure - Shreyas Arya; Melissa L. Kingma; Stacey Dornette; Amy Weber; Cathy Bardua; Sarah Mierke; Paul S. Kingma (Hindawi Limited, 2022)
Background. Airway pressure release ventilation (APRV) is a relatively new mode of ventilation in neonates. We hypothesize that APRV is an effective rescue mode in infants failing conventional ventilation and it is comparable in survival rates to rescue with high-frequency oscillatory ventilation (HFOV). Methods. This is a 6-year retrospective cohort study of infants that failed synchronized intermittent mandatory ventilation (SIMV) and were rescued with either APRV or HFOV. For comparison, we divided infants into two groups (28-37 and >37 weeks) based on their corrected gestational age (CGA) at failure of SIMV. Results. Ninety infants were included in the study. Infants rescued with APRV (n=46) had similar survival rates to those rescued with HFOV (n=44)-28-37 weeks CGA (APRV 78% vs. HFOV 84%, p=0.68) and >37 weeks CGA (APRV 76% vs. HFOV 72%, p=0.74). Use of APRV was not associated with an increase in pneumothorax (APRV 0% and HFOV 10%, p=0.31, in 28-37 weeks CGA, and APRV 0% and HFOV 4%, p=0.22, in >37 weeks CGA). Conclusion. APRV can be effectively used to rescue infants with refractory respiratory failure on SIMV. When compared to HFOV, rescue with APRV is not associated with an increase in mortality or pneumothorax.